Fun English Untuk Siswa Kelas Rendah Di Gubuk Daya Kelayu Utara - Wati, Laila; Maysuroh, Siti; Maulani, Astrid; Yusri, Ahmad (Jurnal Inovasi dan Pengabdian kepada Masyarakat (JIPMas), 2026)
This community service program aimed to improve elementary school students’ interest and basic competence in learning English through the implementation of Fun English Activities in Gubuk Daya, Kelayu Utara Village. The program was conducted due to the absence of English instruction in the local primary school, which limited students’ early exposure to the language. The activities were carried out in the form of tutoring sessions using a play-based learning approach that integrated games, songs, picture-based quizzes, and interactive activities focusing on basic vocabulary, simple expressions, adjectives, and colors. The results indicated that students showed improvement in vocabulary mastery, confidence in speaking, and learning motivation. The use of fun and interactive activities created a positive learning environment and encouraged active participation. Therefore, Fun English Activities proved to be an effective alternative strategy for introducing English to young learners in community-based educational programs.